A comparative study on the position control method of dc servo motor with position feedback by using arduino - Sadun, Amirul Syafiq (2015)
Unlike Direct Current (DC) motors, the DC servo motor’s angular position can be adjusted to a specific angle by using a control signal. Arduino has recently been used in a wide range of control approaches, especially involving closed-loop system with servo motor due to its flexibility and simplicity. In order to control the DC servo motor, there are three different methods that can be used by using Arduino namely Arduino Integrated Drive Electronics (IDE), Support target for Simulink (Support Package) and Arduino Input/Output (IO) Package. This paper presents a comparative study on the servo motor position control (with voltage feedback) by using the above methods to find out the best technique to control the complex servo motor system with closed-loop position feedback